2017
DOI: 10.3122/jabfm.2017.05.170182
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Anorexia Nervosa

Abstract: Eating disorders are not commonly diagnosed in individuals aged >50 years, yet they are associated with significant psychiatric comorbidities and overall morbidity. Anorexia nervosa is the most common eating disorder among this age group, and women are affected most often. We present the fatal case of a 66-year old woman with severe malnutrition and newly diagnosed anorexia nervosa. Inpatient refeeding was unsuccessful, and she succumbed to multisystem organ failure. The timely recognition of eating disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
7
0
5
Order By: Relevance
“…We decided not to set an age limit to achieve a comprehensive epidemiologic view on mortality of patients with AN. Moreover, there are case reports of patients newly diagnosed with AN at the age of 65 or older [32], and a recent study demonstrated that active eating disorders are common amongst women in mid-life, both due to new onset and chronic disorders [33].…”
Section: Mortality For People With Anmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided not to set an age limit to achieve a comprehensive epidemiologic view on mortality of patients with AN. Moreover, there are case reports of patients newly diagnosed with AN at the age of 65 or older [32], and a recent study demonstrated that active eating disorders are common amongst women in mid-life, both due to new onset and chronic disorders [33].…”
Section: Mortality For People With Anmentioning
confidence: 99%
“…One should keep in mind though, while interpreting the results of our study, that a diagnosis of AN did neither require that AN was the leading current diagnosis nor that it was the first episode of AN. Second, current research has highlighted the occurrence of AN in mid-life and older adults [32,33,49]. Third, studies in AN have used different upper age limits, for example, 40 years of age [20,31], even though other studies have shown that in a relevant proportion of people with AN is first diagnosed or first treated after the age of 40 [32,33].…”
Section: Comparison To Previous Researchmentioning
confidence: 99%
“…In the older population, it would be possible to misdiagnose eating disorders as a medical issue or a consequence of an organic problem. Another complicating factor in identification could be that adults are more adept at masking their illness [ 11 ] than their younger counterparts [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that not only can eating disorders exist in the older age group, but that the risk of mortality and morbidity in this age group is significantly higher. Therefore, the timely recognition of eating disorders among older age groups appears to be of great importance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…National epidemiologic surveys show that anorexia nervosa manifests itself during young adulthood. 4 Zayed et al 5 report an exception: a malnourished 66-year-old woman with anorexia nervosa. This case report alerts clinicians in community-based practice to avoid age-related bias when diagnosing a condition with a potentially fatal trajectory.…”
Section: Patient-level Improvementmentioning
confidence: 99%